Gas Transport Properties in Gas Diffusion Layers: A Lattice Boltzmann Study (Communications in Computational Physics, 2020)
The lattice Boltzmann method is applied to the investigations of the diffusivityand the permeability in the gas diffusion layer (GDL) of the polymer electrolytefuel cell (PEFC). The effects of the configuration of water droplets, the porosity of theGDL, the viscosity ratio of water to air, and the surface wettability of the GDL areinvestigated. From the simulations under the PEFC operating conditions, it is foundthat the heterogeneous water network and the high porosity improve the diffusivityand the permeability, and the hydrophobic surface decreases the permeability.